Impact of digital marketing, fintech, and Islamic branding on MSME performance with innovation moderation - Rofiq, Ahmad Nur; Ariyani, Diyah; Muna, Izzatul (Faculty of Business & Economics, Universitas Islam Indonesia, 2024)
Objective – This study aims to analyze the influence of digital marketing, financial technology, and Islamic branching on the performance of Micro, Small Medium Enterprise (MSMEs) in Salatiga City and to test the moderating role of Product Innovation in this relationship.Methodology – This study employed a quantitative approach using a survey method. Data were collected using questionnaires distributed to 100 MSME owners in Salatiga. To analyze the data, multiple regression analysis was applied to test the effects of digital marketing, financial technology, and Islamic branding on MSME performance and to examine the moderating role of product innovation. Statistical tests, such as the F-test and t-test, were used to evaluate the significance of the model and individual variables, respectively, ensuring the robustness of the findings.Findings – The results show that financial technology and Islamic brands have a significant influence on MSME performance. By contrast, digital marketing does not have a significant influence. In addition, Product Innovation does not moderate the relationship between digital marketing, financial technology, and Islamic brands and MSME performance.Implications – These findings provide insights for MSMEs and policymakers regarding the importance of optimizing the use of financial technology and strengthening Islamic branding to improve business performance. However, product innovation must be managed more strategically to have a stronger impact on MSME performance.Originality – This study makes a novel contribution by exploring the moderating role of product innovation in the relationship between modern business strategies and MSME performance in Salatiga and highlighting the local context relevant to the cultural and economic diversity in this city.